Common Fixed Point Theorems of Ciric Type Weak Contractions in Cone Metric Spaces: G.V.R. Babu, P.D. Sailaja - Team, Support (Thai Journal of Mathematics, 2012)
We prove the existence of common fixed points for a pair of weakly compatible selfmaps satisfying Ciric type weak contractions in cone metric spaces where the underlying cone is neither regular nor normal. Our theorems extend the results of Choudhury and Metiya [B.S. Choudhury, N. Metiya, Fixed points of weak contractions in cone metric spaces, Nonlinear Anal. 72 (2010) 1589–1593] to non-normal cones. Several examples are provided in support of our results.